The Dark Side of Indonesia’s Democracy: Does Pancasila still hold influence? - Abdurrahman, Tama (Indonesian Journal of Pancasila and Global Constitutionalism, 2024)
Indonesia's transition to democracy has been celebrated globally, yet beneath the surface lies a complex interplay between democratic principles and the enduring influence of Pancasila, the state ideology. This paper delves into the less-explored facets of Indonesia's democracy, probing whether Pancasila still exerts significant influence in shaping the country's political landscape. The analysis begins by contextualizing Indonesia's democratic journey, tracing its evolution from the authoritarian era to the present. It then examines the foundational principles of Pancasila and their historical significance, emphasizing its role as a unifying force amidst Indonesia's diverse socio-cultural landscape. Drawing on recent political developments, the paper investigates instances where Pancasila's influence intersects with democratic ideals, as well as instances where tensions arise. It explores how Pancasila has been invoked both to promote national unity and to justify restrictions on dissent and minority rights. Furthermore, the paper assesses the implications of Pancasila's enduring influence on Indonesia's democratic governance, particularly in relation to issues of political pluralism, freedom of expression, and minority rights. It highlights the challenges of reconciling Pancasila's collectivist ethos with democratic principles of individual rights and freedoms. Through this analysis, the paper contributes to a deeper understanding of Indonesia's democracy by shedding light on its complexities and contradictions. It underscores the need for critical reflection on the role of Pancasila in shaping democratic norms and practices, urging for a nuanced approach that upholds democratic principles while honoring Indonesia's unique socio-cultural heritage.